Face-Threatening Acts on Illocutionary Utterances in the Third US Presidential Debate of 2016 - Rudi Rahman (Universitas Brawijaya, 2019)
This research aims to investigate the face-threatening acts (FTAs) on illocutionary utterances found in a 2016 US presidential debate. A descriptive qualitative approach and document analysis were applied in this research. The data source of this research is the transcript of the last debate of the US presidential election in 2016. The illocutionary utterances were identified and categorized based on the five types of illocutionary utterances in Austin and Searle’s theory, and the data were analyzed using Brown and Levinson’s theory of FTAs. The result shows the illocutionary utterances that contain most FTAs are expressive illocutionary utterances (40.62%), directive illocutionary utterances (20.83%), assertive illocutionary utterances (17.70%), commissive illocutionary utterances (16.66%), and declarative illocutionary utterances (4.16%). Next, the most common FTAs the debater performs are the speaker’s negative face (33 times), followed by the hearer’s positive face, the hearer’s negative face, and the speaker’s positive face. This research has also shown that the speaker’s positive face does not always threaten the hearer’s positive or negative face, and vice versa.